Assessment of stress-strain behavior of energy piles installed in sand - Dubey A.A.; Kumar S. (My University, 2025)
The geothermal piles are dual functional geostructures which provide sub-structural support to the building and also fulfill the energy demands in terms of its climate control. For efficient design of geothermal piles, it is necessary to evaluate the thermo-mechanical behavior of geothermal piles. The purpose of this study is to evaluate the behavior of geothermal heat exchanger pile installed in sand, subjected to a coupled thermo-mechanical loading. Initially, in this study a full scale field test is simulated and results are compared. In the second phase, parametric study by varying mechanical and thermal loading on the geothermal pile placed in dense sand, is performed. In this study, the sand and geothermal pile are simulated as axis-symmetrical models, where pile is considered to be thermo-elastic in nature and sand is considered as Mohr-Coulomb elastic-plastic material. Coupled Temperature-Displacement analysis is applied in order to simulate the observed experimental results. It is shown that the simulated model is able to reproduce the major thermo-mechanical effects for the selected full scale model approximately. Stress and strain behavior along with the depth of energy pile induced by thermo-mechanical loading has been reported. It was concluded that when mechanical load value is comparatively low, the thermal variation influences the induced axial stress while at higher mechanical load the stress behaviour is nearly constant at different temperature variation. © Int. J. of GEOMATE. All rights reserved.